Precision Antifungal Treatment Significantly Extends Voice Prosthesis Lifespan in Patients Following Total Laryngectomy - Pentland, Daniel R.; Stevens, Sarah; Williams, Leila; Baker, Mark; McCall, Carolyn; Makarovaite, Viktorija; Balfour, Alistair; Mühlschlegel, Friedrich A.; Gourlay, Campbell W. (Frontiers in Microbiology, 2020)
Indwelling silicone valves called voice prostheses (VPs) are the gold standard for speech rehabilitation in patients with laryngeal cancer following total laryngectomy. Reported VP lifespans amongst these patients are highly variable but when devices fail patients experience loss of voice and an increase risk of chest infection. Early failure of VP is a current clinical concern that is associated with regular hospital visits, reduced quality of life and associated medical cost. Poly-microbial biofilms comprised of both bacterial and fungal microorganisms readily colonise VPs and are linked to loss of device performance and its early failure in addition to providing a reservoir for potential infection. Our detailed analysis of poly-microbial biofilm composition on 159 early failing VPs from 48 total laryngectomy patients confirmed Candida albicans as the predominant fungal species and Staphylococcus aureus as the most common bacterial coloniser within our patient cohort. Using a combination of microbiological analysis, patient data and a high-throughput antifungal test assay mimicking in-vivo conditions we established an evidence based precision antifungal treatment approach to VP management. Our approach has allowed us to implement a personalized VP management pathway, which increases device in situ lifespan by an average of 270%. Our study represents a significant step forward in both our understanding of the cause of VP failure and a new effective treatment pathway that offers tangible benefit to patients.